Sarcopenia en la pérdida funcional: rol del ejercicio - Molina Y., Juan Carlos (Revista Hospital Clínico Universidad de Chile, 2008)
Sarcopenia is refers to the gradual decline in muscle mass and quality noted with advancing age, but is not only present in that’s condition. In the last time appear new names proposal how myoestheatosis of the aging in reference at changes in the fat composition of the mass muscle. Factors implicated in the etiology of sarcopenia include decreased physical activity, malnutrition, increase inflammatory activity, oxidative stress and abnormalities in the hormonal and the vitamin axes and others. There is growing evidence linking sarcopenia to the frailty and functional disability, falls, decreased bone density, glucose intolerance contributes significantly to the morbidity, decrease in quality of life, and health care cost in the elderly. Exercise has been shown to increase strength, aerobic capacity, and muscle protein synthesis, in both young and older people, however, exercise does not reverse all age – related changes, but is a strong tool for maintain the autonomy. In special of the strength and resistence together with adequate nutritional state.